The Influence of Music on Health and the Development of Culture and Art in Uzbekistan (Texas Journal of Multidisciplinary Studies, 2022)
Music is a special form of culture that has its meaning, a set of images, mechanisms of influence both on a person and on society. Influencing all the structural and semantic foundations of society and personality, it specifically affects the psycho-physiological state of a person. Because of this, music acts as a biological and anthropological constant, which transforms it into a sense-forming element of the environmental friendliness of the existence of the individual.